2016
DOI: 10.1016/j.pnpbp.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Resting state vagal tone in borderline personality disorder: A meta-analysis

Abstract: Borderline personality disorder (BPD) is the most common personality disorder in clinical settings. It is characterized by negative affectivity, emotional liability, anxiety, depression, as well as disinhibition (i.e., impulsivity and risk taking), all of which have been linked to lower resting state vagal tone, which may be indexed by vagally-mediated heart rate variability (vmHRV). Here, we aimed to quantify the current evidence on alterations in resting state vmHRV in individuals with BPD, relative to healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 100 publications
(148 reference statements)
8
69
0
3
Order By: Relevance
“…Associations with emotional adjustment are well documented. Higher resting vmHRV is associated with less negative affect and more constructive coping in response to daily stressors (Fabes & Eisenberg, ), whereas low resting vmHRV is associated with emotional symptoms and disorders, including depression (Kemp et al, ), anxiety (Chalmers, Quintana, Abbott, & Kemp, ), posttraumatic stress disorder (Campbell, Wisco, Silvia, & Gay, ), and borderline personality (Koenig, Kemp, Feeling, Thayer, & Kaess, ), suggesting a transdiagnostic marker of psychopathology and related vulnerabilities (Beauchaine & Thayer, ). Such associations are similar in children and adolescents (e.g., Koenig, Kemp, Beauchaine, Thayer, & Kaess, ).…”
Section: Empirical Findingsmentioning
confidence: 99%
“…Associations with emotional adjustment are well documented. Higher resting vmHRV is associated with less negative affect and more constructive coping in response to daily stressors (Fabes & Eisenberg, ), whereas low resting vmHRV is associated with emotional symptoms and disorders, including depression (Kemp et al, ), anxiety (Chalmers, Quintana, Abbott, & Kemp, ), posttraumatic stress disorder (Campbell, Wisco, Silvia, & Gay, ), and borderline personality (Koenig, Kemp, Feeling, Thayer, & Kaess, ), suggesting a transdiagnostic marker of psychopathology and related vulnerabilities (Beauchaine & Thayer, ). Such associations are similar in children and adolescents (e.g., Koenig, Kemp, Beauchaine, Thayer, & Kaess, ).…”
Section: Empirical Findingsmentioning
confidence: 99%
“…Bulimia nervosa (BN) is associated with various mental comorbidities, in particular depression and anxiety disorders as well as borderline personality disorder (Blinder, Cumella, & Sanathara, 2006;Cassin & von Ranson, 2005). Reduced vagally mediated HRV relative to controls is reported in both depressive disorders (Kemp et al, 2010) and anxiety disorders (Chalmers, Quintana, Maree, Abbott, & Kemp, 2014) including social anxiety as well as borderline personality disorder (Koenig, Feeling, Kemp, Thayer, & Kaess, 2016). It may be hypothesized that direct gastrointestinal effects brought about by bingeing and various compensating behaviours in BN exert a more prominent influence on the PNS than psychological symptoms and psychiatric comorbidities, respectively.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Chronic reductions in vagal activity indexed by HRV are associated with poor physiological, emotional, cognitive, behavioral regulation and self-rated heath (Alvares et al 2013; Beauchaine and Thayer 2015; Jarczok et al 2015; Thayer and Lane 2000; Thayer et al 2012; Thayer et al 2009a; Thayer and Lane 2009), as well as psychopathology (Kemp et al 2010; Koenig et al 2015, 2016; Clamor et al 2016). Functional neuroimaging studies and human lesion studies have shown several brain regions and networks involved in the neural control of HRV (Thayer et al 2012).…”
Section: Introductionmentioning
confidence: 99%